Effect of interfacial modifiers and wood flour treatment on the rheological properties of recycled polyethylene/wood flour composites. Issue 1 (February 2020) - Hong, Haoqun; Guo, Quannan; Zhang, Haiyan; He, Hui
The article presents the preparation of a high-performance wood–plastic composites with improved interfacial interactions by adding ternary-monomer graft copolymers as the interfacial modifiers and by braising wood flour (WF) and investigates their effects on the rheological properties of recycled polyethylene (rPE)/WF composites. The processing properties, capillary rheological properties, dynamical rheological properties, and mechanical properties were investigated. Results show that graft copolymer of polyethylene is effective in improving the interfacial interactions of rPE/WF composites, dramatically changing the rheological and mechanical properties. The braising of WF enlarges the gaps of cells and promotes the infiltration of rPE into the gaps, as promoting the increasing in mechanical properties of rPE/WF composites and significantly changing the rheological properties of the composites.